AGRONOMIC FEASIBILITY OF POLYCULTURES OF ARUGULA/CARROT/LETTUCE UNDER AMOUNTS OF ROOSTERTREE AND POPULATION DENSITIES - Oliveira, Lenilton Alex de Araújo (2015)
This work aimed to study the agronomic feasibility of the arugula (A) and lettuce (L) bicropping intercropped with carrot (C) under different amounts of roostertree incorporated into the soil and proportions of population densities among component crops in semiarid conditions of the Rio Grande do Norte state. The experimental design was randomized complete block with four replications, with the treatments arranged in a factorial 4 x 4. The first factor was constituted by the amounts of roostertree incorporated into the soil (10, 25, 40 and 55 t ha-1 on a dry basis) and the second factor by the proportions of population densities of the component crops in polyculture [(50A-50C-50L (%); 40A-50C-40L (%); 30A-50C-30L (%) and 20A-50C-20L (%) of the recommended populations in sole crops - RPSC)]. The leafy vegetable crops were planted in two cultivations during the carrot cycle, and a joint analysis was carried out involving the two cultivations in the 4 x 4 factorial scheme. The characteristics evaluated were green mass yield (arugula), dry mass of shoots and productivity (lettuce), total, commercial and classified productivity of carrot roots. The modified monetary advantage was used to evaluate the agronomic feasibility of intercropping systems. The use of roostertree as green manure proved viable in the polyculture of arugula, carrot, and lettuce. The major agronomic performance of the arugula, carrot and lettuce in the polyculture was registered in the amount of 55 t ha-1 of roostertree incorporated into the soil. The population density proportions of arugula, carrot and lettuce of 50A-50C-50L (%) of the RPSC were those that provided the greatest agronomic feasibility of the polycultures.